Research on fluoride removal from membranes rejected water - Boussouga, Youssef-Amine; Valentukevičienė, Marina; Zurauskienė, Ramunė (International Conference “Environmental Engineering”, 2017)
The excess of fluoride in water intended for human consumption can cause some problems in health of consumers from concentrations over than 1.5 mg/L. A detailed study has been carried out for the removal of fluoride from concentrated rejected water overcoming the drawback of membrane processes by using sorption techniques. Opoka mineral which is a natural sorbent and polonite have been chosen and valorized in this present work as fluoride sorbents for rejected water by membranes of the water treatment plant. These sorbents have been selected in order to reduce the treatment cost and to meet the standards of rejected water especially in term of fluoride. Opoka sorbent and polonite have shown effective results for fluoride removal from rejected water with efficiency over than 77%. In order to understand the sorption phenomenon and to validate the results with sorbents, we have applied experimental data on Freundlich Isotherm and SEM microscopic technique.